Literature and stylistics for language learners: theory and practice - Watson, Greg; Zyngier, Sonia (Palgrave Macmillan, 2007)
Stylistics in second language contexts / Geoff Hall -- On teaching literature itself / Peter Stockwell -- When the students become the teachers / Joanne Gavins and Jane Hodson -- The shudder of the dying day in every blade of grass / John McRae -- Analysing literature through films / Rocio Montoro -- Discourse stylistics and detective fiction / Urszula Clark -- Corpus stylistics as a discovery procedure / Donald E. Hardy -- Literary worlds as collocation / Bill Louw -- Investigating student reactions to a web-based stylistics course in different national and educational settings / Mick Short, Beatrix Busse and Patricia Plummer -- From syntax to schema / David L. Gugin -- Non-standard grammar in the teaching of language and style / Paul Simpson -- Language teaching through gricean glasses / Judit Zerkowitz -- Attention-directed literary education / David Ian Hanauer -- What reading does to readers / Willie van Peer and Aikaterini Nousi -- Revisiting literary awareness / Sonia Zyngier, Olivia Fialho and Patricia Andrea do Prado Rios
Formerly CIP
Includes bibliographical references and index
Keywords: Aufsatzsammlung; Fremdsprachenlernen; Stilistik